1996
DOI: 10.1128/jb.178.21.6288-6295.1996
|View full text |Cite
|
Sign up to set email alerts
|

Two types of novel dipeptidyl aminopeptidases from Pseudomonas sp. strain WO24

Abstract: Two kinds of dipeptidyl aminopeptidase I (DAP I [cathepsin C])-like activities which hydrolyzeGly-Phe-pnitroanilide (Gly-Phe-pNA) were detected in Pseudomonas sp. strain WO24. They were purified and characterized. The isolated enzymes, named DAP BII and DAP BIII, were revealed to be homogeneous by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) and isoelectric focusing. DAP BII was estimated to have a molecular mass of 150,000 Da by gel filtration and a subunit size of 73,000 Da by SDS-PAG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
20
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 26 publications
(24 reference statements)
3
20
0
Order By: Relevance
“…Recently, we have reported the identification, purification, and characterization of novel dipeptidyl aminopeptidases (DAPs) named DAP BI,25) DAP BTI, and DAP BITI, 26) and of a ubiquitous DAP IV 27 ) from Pseudomonas sp. W024.…”
mentioning
confidence: 99%
“…Recently, we have reported the identification, purification, and characterization of novel dipeptidyl aminopeptidases (DAPs) named DAP BI,25) DAP BTI, and DAP BITI, 26) and of a ubiquitous DAP IV 27 ) from Pseudomonas sp. W024.…”
mentioning
confidence: 99%
“…On the basis of the enzymological data that we obtained, we proposed that bacterial DAPs should be classified in a manner different from that of mammalian DPPs, except for DAP IV (Ogasawara, Kobayashi et al, 1996). We have also characterized a prolyl oligopeptidase (POP) from P. mexicana WO24 (unpublished data) and demonstrated that DAP BI, DAP BIII, DAP IV and POP belong to the POP family (Kanatani et al, 1991;Rawlings et al, 1991) and are classified into clan SC, family S9 in the MEROPS database (Rawlings et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…We have reported the identification, purification and characterization of DAP BI (bacterial dipeptidyl aminopeptidase; Ogasawara, Ochiai et al, 1996;Ogasawara et al, 1998), DAP BII (Ogasawara, Kobayashi et al, 1996), DAP BIII (Ogasawara, Kobayashi et al, 1996) and DAP IV (Ogasawara, Ogawa et al, 1996;Ogasawara et al, 2005) from Pseudoxanthomonas mexicana WO24, which is a Gram-negative aerobic bacterium isolated from the wastewater of a bean curd (tofu) factory. On the basis of the enzymological data that we obtained, we proposed that bacterial DAPs should be classified in a manner different from that of mammalian DPPs, except for DAP IV (Ogasawara, Kobayashi et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…DPP IV (EC 3.4.14.5), a serine protease with an optimum pH of 8-9, specifically cleaves gly-pro from the N-termini of its substrates. Several DPPs, including some with specificities different from those in mammals, have recently been identified in microorganisms (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) including Dictyostelium discoideum (13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…DPP II (EC 3.4.14.2), a serine protease with an acidic optimum pH of 4.5-6, preferentially cleaves dipeptides from the N-termini of X-ala-or X-pro-NA. DPP III (EC 3.4.14.4) is a serine protease with an optimum pH of [8][9][10].…”
Section: Introductionmentioning
confidence: 99%